Separation of the alkaloids of Citrus grandis - Cruz, Resurreccion I.
The dried root bark of Citrus grandis was extracted with ethanol and this was partitioned between chloroform and water with the ratio of 1:3:1 (extract:water:chloroform). The chloroform layer was used for the separation of the alkaloids.